Project of technical standards for pomegranate integrated production in Valencia - Albujer E.; Toledo J. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
Norms are drawn up to be followed in crop husbandry, type of plant material, fertilization, irrigation, cultivation techniques and in particular phytosanitary protection. Norms include methods for monitoring pests and their evolution, techniques for pest control, authorized pesticides, consideration of toxicity for users as well as repercussion on the beneficiary fauna and residues.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)